Comment on 'How long is my toilet roll-a simple exercise in mathematical modelling'. Issue 9 (21st October 2021) - Arribas, E.; Escobar, I.; Ramirez-Vazquez, R.
Abstract : In the article 'How long is my toilet roll-a simple exercise in mathematical modelling' several models of increasing complexity are introduced and solved to calculate indirectly the length of paper on a toilet-roll. All these results are presented without errors. The authors of this comment believe the error analysis of measurements made in a laboratory is an important part of the experiment. The calculation of the absolute errors in indirect measurements provides us with information about the confidence that we must have in our experimental results. For that reason, the error calculation for all approximations has been made.